Pengaruh Citra Merek dan Ulasan Pelanggan terhadap Keputusan Pembelian Teh Gambir dengan Harga sebagai Variabel Intervening Pada UD. Sondel di Kabupaten Pakpak Bharat - Darwis Solin; Riny Chandra; Tengku Putri Lindung Bulan (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to determine the influence of brand image and customer reviews on the purchasing decision of Gambir tea, with price as an intervening variable at UD. Sondel in Pakpak Bharat Regency. This research is quantitative with the population consisting of residents of Pakpak Bharat Regency. The sampling technique used is purposive sampling, with a total of 100 respondents. The data were processed using SPSS version 26, with analysis methods including classical assumption testing, path analysis, Sobel test, and hypothesis testing. The results of the study indicate that: (1) brand image has a direct significant effect on price, (2) customer reviews have a direct significant effect on price, (3) brand image has a direct significant effect on purchasing decisions, (4) customer reviews have a direct significant effect on purchasing decisions, (5) price has a direct significant effect on purchasing decisions, (6) brand image has an indirect significant effect on purchasing decisions through price, and (7) customer reviews have an indirect significant effect on purchasing decisions through price.